Distress tolerance and reactivity to negative affective cues in naturalistic environments of cannabis-using emerging adults. (1st September 2022) - Gex, Kathryn S.; Gray, Kevin M.; McRae-Clark, Aimee L.; Saladin, Michael E.; Tomko, Rachel L.
Abstract: Background: Distress tolerance (DT) has been implicated as an important factor in the experience of negative affect (NA) and cannabis craving. However, previous research is limited by its use of laboratory paradigms that may not replicate in naturalistic settings. The current study examined how DT influenced reactivity to NA cues in daily life in a sample of frequent (≥3 times per week) cannabis-using emerging adults (age 18–21). Methods: Using cue-reactivity ecological momentary assessment (CREMA), 63 (54 % female; 85.7 % white; M age = 19.62) participants reported on their cannabis craving and affect (sadness, relaxation) four semi-random times per day for two weeks (56 possible CREMA sessions/participant). We assessed affect and cannabis craving before and after exposure to neutral and NA cues. Multilevel modeling was used to examine within- and between-participant effects of cues, DT, and sex, as well as within- and between-participant average pre-cue affect and craving, on post-cue affect and craving. Results: NA cues consistently predicted higher-than-normal post-cue sadness and lower relaxation, but not greater-than-normal post-cue craving. Cue type interacted with sex and DT to predict post-cue sadness, but not craving. Female participants and those reporting low DT reported higher sadness following NA cues compared to males and those with high DT, respectively. Conclusions: Frequent cannabis-using emerging adults differed in affect, but not cannabis craving, reactivity to NA cues as a function of sex and DT. Our results were partially consistent with prior human laboratory and CREMA research finding greater reactivity to NA cues among females and individuals with low DT. Highlights: Few studies of distress tolerance on cue reactivity in cannabis-using individuals. Novel use of Cue Reactivity Ecological Momentary Assessment (CREMA) methodology. Brief CREMA cues can induce negative affect in the naturalistic environment. Distress tolerance and sex associated with affective cue reactivity.